A low dielectric loss tangent ceramic material for system-level packaging and a preparation method thereof
By adding specific additives to ceramic raw materials, the sintering temperature is reduced, and the Al2O3/Aln compound -phase ceramic material is formed, solving the problem of high cost and large conductor loss in the high temperature sintering process of existing ceramic packaging materials. Comprehensive performance with high curved strength and low thermal expansion coefficient.
Patent Information
- Application Number
- CN202411506032.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing ceramic packaging materials have high costs and high conductor losses during high-temperature sintering. The flexural strength of low-temperature co-fired ceramic materials is insufficient, making it difficult to meet the application requirements in the fields of high-speed and high-frequency.
By adding cordierite powder, CBS powder and rare earth oxides to ceramic raw materials, the sintering temperature is reduced to form Al2O3/AlN composite phase ceramic materials, achieving comprehensive properties of low dielectric loss, high flexural strength and low thermal expansion coefficient.
It achieves the formation of dense structure ceramic materials at lower sintering temperatures, with ideal dielectric properties, mechanical properties and thermal properties, reducing production costs, and improving the reliability of materials and the flexibility of packaging forms.
Smart Images

Figure CN119019158B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials for packaging, and relates to a low dielectric loss tangent ceramic material for system-level packaging and a preparation method thereof. Background Art
[0002] In recent years, electric vehicles, electric locomotives, semiconductor lighting, aerospace, satellite communications, etc. have entered a stage of rapid development, and electronic components are developing towards high power, high frequency, and integration. Alumina ceramics are widely used in military communications, remote sensing and telemetry electronic countermeasures, optoelectronic technology, etc. due to their high volume resistivity, high flexural strength, high hardness, low dielectric loss, small linear expansion coefficient, high insulation performance, and the ability to be welded and sealed with metals. They have become an indispensable and important raw material for the production of microelectronic devices and optoelectronic devices.
[0003] The sintering temperature of conventional alumina ceramics is above 1500℃, which has high requirements for sintering equipment. It requires a high-temperature hydrogen sintering furnace and consumes a lot of energy, such as electricity and hydrogen, so the manufacturing cost has always been high. In addition, the high sintering temperature also limits it to using refractory metals such as W and Mo as conductor materials. The metallization resistance of W and Mo materials is large, and the conductor loss is high, which cannot fully meet the application in high-speed and high-frequency fields. Although LTCC (low-temperature co-fired ceramic material) can use low-resistance conductors such as gold, silver, and copper, a large amount of glass components are added to reduce the sintering temperature, resulting in its bending strength of less than 200MPa. The reduction in bending strength leads to a decrease in its reliability. It is easy to crack or break under a slightly larger impact, causing serious failure of the product. In addition, the low bending strength of LTCC also limits the thickness of the packaging substrate, which is not conducive to the application of ultra-thin packaging, thereby limiting the further miniaturization of the package.
[0004] CN110128117B discloses a high-purity alumina ceramic material and a preparation method thereof, and the main process flow is as follows: high-purity alumina ball milling, spray granulation, isostatic pressing, green body processing, high-temperature sintering into porcelain, grinding, metallization, brazing, and polishing. CN115321960B discloses an alumina ceramic and its preparation method and application, which relates to the technical field of alumina ceramics. The technical scheme provides a preparation method of alumina ceramics, comprising the following steps: (1) preparing an alumina ceramic blank; (2) transferring the alumina ceramic blank obtained in step (1) to a microwave hot isostatic pressing furnace for sintering, and cooling to obtain the alumina ceramics. CN110423102A discloses a ceramic packaging shell material suitable for low-resistance leads, which is composed of the following weight percentages: 6-12% silicon dioxide, 1-3% calcium fluoride, 1-2% borax, 2-5% barium oxide, 0.5-1% potassium oxide, 6-15% colorant, and alumina.
[0005] In order to ensure the stability of the working process of electronic components, very high requirements are placed on the mechanical properties, dielectric properties and thermal properties of packaging materials. However, the current traditional packaging ceramic materials cannot meet the increasingly stringent working environment requirements. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low dielectric loss tangent ceramic material for system-level packaging and a preparation method thereof. By adding cordierite powder, CBS powder and rare earth oxides to the raw materials, the sintering temperature of the ceramic raw materials is greatly reduced, and a ceramic material with a dense structure can be formed at a relatively low sintering temperature. Finally, an Al2O3 / AlN composite ceramic material with ideal dielectric properties and mechanical properties is prepared.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, the preparation method comprising:
[0009] Alumina, aluminum nitride, cordierite powder, CBS powder and rare earth oxide are uniformly mixed to obtain a precursor mixture; the precursor mixture, abrasive balls and deionized water are mixed and wet-milled to obtain a precursor wet material, the precursor wet material is dried and sieved to obtain a precursor dry powder; the precursor dry powder is mixed with a polyvinyl butyral solution to obtain a precursor solution; the precursor solution is spray-granulated to obtain a precursor powder; the precursor powder is placed in a mold for tableting to obtain a green body; the green body is heated to a debinding temperature and kept warm, and is continuously heated to a first sintering temperature and kept warm, and then is cooled to a second sintering temperature and kept warm, and after the insulation is completed, the green body is cooled to a furnace outlet temperature and taken out, and is cooled outside the furnace to room temperature to obtain the low dielectric loss tangent ceramic material.
[0010] Ceramic materials for packaging need to have the characteristics of low dielectric loss, high flexural strength and low thermal expansion coefficient. Alumina has the characteristics of good dielectric properties, high flexural strength and good chemical corrosion resistance. Aluminum nitride has the characteristics of low dielectric loss, low thermal expansion coefficient, high insulation resistance and high thermal conductivity. The present invention uses alumina and aluminum nitride as the main ceramic raw materials for ceramic materials for packaging. By adding cordierite powder, CBS powder and rare earth oxides to the ceramic raw materials, the sintering temperature of the ceramic material is greatly reduced. A ceramic material with a dense structure can be formed at a relatively low sintering temperature, and finally an Al2O3 / AlN composite ceramic material with ideal dielectric properties, mechanical properties and thermal properties is prepared.
[0011] Since AlN is a covalent bond structure compound with a small self-diffusion coefficient, it needs to be sintered at a higher temperature (>1800°C) to form a ceramic material with a dense structure. Due to the high sintering cost, aluminum nitride materials are difficult to be widely used in packaging materials. The present invention achieves low-temperature sintering by adding cordierite powder, CBS powder and rare earth oxides as sintering aids to the ceramic raw materials. A ceramic material with high density can be sintered within a sintering temperature range of 1500-1600°C. The low-temperature sintering process not only greatly reduces the production cost of the sintering process, but also the low-temperature sintering can delay the diffusion rate of surface oxygen atoms to the interior of the AlN lattice to a certain extent, improve the purification effect of the aluminum nitride lattice during the sintering process, and is conducive to the preparation of packaging ceramic materials with both dielectric properties, mechanical properties and thermal properties.
[0012] The theoretical chemical composition of cordierite is 2MgO·2Al2O3·5SiO2, which has a low thermal expansion coefficient, high chemical stability and strong mechanical strength. The present invention adds an appropriate amount of cordierite powder to the ceramic raw material, which not only improves the disadvantage of low thermal expansion coefficient of alumina, but also significantly reduces the sintering temperature of the ceramic material. This is because, on the one hand, cordierite can form a low-melting-point eutectic compound with alumina during the sintering process, and the low-melting-point eutectic compound will produce a liquid phase when the lowest eutectic temperature is reached during the sintering process, that is, the liquid phase will be produced before the sintering temperature is reached. The liquid phase flow mass transfer is utilized to reduce the sintering temperature of the ceramic material and promote the structural densification of the fired ceramic material; on the other hand, cordierite will promote the reaction between Al2O3 and AlN to generate a new phase of Al5O6N during the sintering process, and at the same time produce a liquid phase, so that the sintering temperature of the Al2O3 / AlN composite ceramic material is reduced by about 200°C.
[0013] CBS powder, as a low-melting-point glass phase, is compositely sintered with ceramic phases such as Al2O3, AlN and cordierite powder to obtain a ceramic material with good dielectric and thermal properties. During the sintering process, as the low-melting-point glass phase softens and melts, it wets and dissolves Al2O3, AlN and cordierite powders, thereby accelerating the mass transfer rate of the raw powder particles into the glass phase, increasing the liquid phase content, and reducing the viscosity. The gradually increasing liquid phase can better wet and fill the gaps between the raw powder particles, so that capillary action is generated in the gaps between the raw powder particles. When the liquid phase wets the raw powder particles, the capillary pressure formed in the gaps between the raw powder particles allows the liquid phase to quickly enter and fill the gaps between the raw powder particles. The internal structure of the fired ceramic material is made denser through the liquid phase diffusion, thereby greatly reducing the dielectric loss and thermal expansion coefficient of the ceramic material.
[0014] The present invention adds rare earth oxides to the ceramic raw materials as stabilizers and sintering aids in the sintering process, which can produce a synergistic effect with cordierite powder and CBS powder, thereby further promoting the densification degree of the ceramic material, reducing the dielectric loss of the ceramic material and significantly improving the mechanical properties of the ceramic material. This is because, on the one hand, the rare earth oxides can promote the reaction of Al2O3 with cordierite powder and CBS powder to generate a liquid phase with a lower melting point, thereby increasing the liquid phase yield; at the same time, the radius of rare earth ions is relatively large and it is difficult to form a solid solution with Al2O3, so the rare earth elements mainly exist in the liquid phase, which is beneficial to reducing the viscosity of the liquid phase. Under the action of capillary pressure at the gaps between raw material powder particles and grains, a large amount of low-viscosity The liquid phase can quickly diffuse and fill the gaps between the raw material powder particles, accelerate the gas discharge, promote the sintering and densification of the ceramic material, and help to further reduce the dielectric loss of the ceramic material; on the other hand, due to the large difference in the ionic radius between the rare earth ions and the aluminum ions, it is difficult for the rare earth elements to dissolve in Al2O3. Therefore, during the sintering process, the rare earth elements mainly exist in the glass phase at the grain boundary. At the same time, the large volume of the rare earth oxides with a glass network structure leads to a high migration resistance in the grain boundary, which hinders the migration of other ions and reduces the grain boundary migration rate. Therefore, the addition of rare earth oxides can effectively inhibit the abnormal growth of grains during the sintering process, refine the grains, and achieve the purpose of improving the mechanical properties of ceramic materials.
[0015] In order to promote the solid phase sintering reaction of raw materials, generally speaking, the particle size of raw material powder particles is finer, but if the particle size of raw material powder particles is too small, its specific area is larger, thereby causing the friction between raw material powder particles to be significantly improved, and fluidity will deteriorate. In the tableting process, raw material powder particles with poor fluidity are difficult to be evenly distributed and fully filled into the mold, thereby causing the green body obtained after tableting to have defects such as non-dense edges around, powder falling, pores, and fractures. In order to solve this problem, the present invention mixes the precursor dry powder with a binder polyvinyl butyral solution before tableting and sprays granulation to obtain a precursor powder, then tablets are formed to the precursor powder, and finally the green body obtained after tableting is sintered. The process route adopted by the present invention can ensure that the raw material powder particles obtain a large contact area while also maintaining the structural integrity of the green body.
[0016] The sintering process is one of the most important steps in the preparation of ceramic materials. The conventional one-step sintering process will cause secondary growth of grains in the later stage of the sintering process, which will lead to a decrease in the performance of the ceramic material. The present invention adopts a two-step atmospheric pressure sintering process to prepare a ceramic material with excellent comprehensive performance. Compared with the conventional one-step sintering process, the two-step atmospheric pressure sintering process adopted by the present invention heats up to the first sintering temperature at a faster heating rate, and then after a short insulation time, it quickly cools down to a second sintering temperature 100-200°C lower than the first sintering temperature, and keeps the temperature at the second sintering temperature for a long time, the purpose of which is to suppress the grain boundary displacement while maintaining the active state at the grain boundary diffusion, so as to achieve the purpose of hindering the abnormal growth of grains and ensure the acquisition of a ceramic material with an ideal density.
[0017] As a preferred technical solution of the present invention, the cordierite powder is prepared by the following method:
[0018] Calcined talc, calcined kaolin, aluminum hydroxide, vanadium pentoxide and calcium fluoride are mixed evenly to obtain cordierite precursor powder; the cordierite precursor powder, abrasive balls and deionized water are mixed and wet-milled to obtain cordierite precursor wet material; the cordierite precursor wet material is dried to obtain cordierite precursor dry material; the cordierite precursor dry material is calcined, ground and sieved in sequence to obtain the cordierite powder.
[0019] As a preferred technical solution of the present invention, the calcined talc is prepared by the following method:
[0020] The talc particles are heated to 1000-1200°C and kept warm for 3-5 hours, and then cooled to room temperature with the furnace to complete calcination. The calcined talc particles are crushed, ground and sieved to obtain the calcined talc, wherein the heating temperature can be 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, 1120°C, 1140°C, 1160°C, 1180°C or 1200°C, and the holding time can be 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h or 5.0h, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In some optional examples, the calcined kaolin is prepared by the following method:
[0022] The kaolin particles are heated to 900-1000°C and kept warm for 1-2 hours, cooled to room temperature with the furnace to complete calcination, and the calcined kaolin particles are crushed, ground and sieved to obtain the calcined kaolin, wherein the heating temperature can be 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C or 1000°C, and the holding time can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] In some optional examples, the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is (37~38):(48~49):(19~20), for example, it can be 37:48:19, 37.1:48.1:19.1, 37.2:48.2:19.2, 37.3:48.3:19.3, 37.4:48.4:19.4, 37.5:48.5:19.5, 37.6:48.6:19.6, 37.7:48.7:19.7, 37.8:48.8:19.8, 37.9:48.9:19.9 or 38:49:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional examples, the particle size D90 of the calcined talc is 18-20 μm, for example, it can be 18 μm, 18.2 μm, 18.4 μm, 18.6 μm, 18.8 μm, 19 μm, 19.2 μm, 19.4 μm, 19.6 μm, 19.8 μm or 20 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional examples, the particle size D90 of the calcined kaolin is 2~3μm, for example, it can be 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm or 3.0μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional examples, the ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass of the vanadium pentoxide is 1:(0.03~0.05), for example, it can be 1:0.03, 1:0.032, 1:0.034, 1:0.036, 1:0.038, 1:0.04, 1:0.042, 1:0.044, 1:0.046, 1:0.048 or 1:0.05, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] The present invention adds vanadium pentoxide to the cordierite raw material. When the amount of vanadium pentoxide added is within the numerical range specified in the present invention, the dielectric loss and thermal expansion coefficient of the fired cordierite powder can be effectively reduced. However, when the amount of vanadium pentoxide added exceeds the upper limit of the range specified in the present invention, the dielectric loss and thermal expansion coefficient of the calcined cordierite powder begin to increase. This is because vanadium pentoxide is easily soluble in water and easily decomposes at high temperatures to form V with high chemical activity. 5+ It can act as a sintering aid during the calcination process, thereby producing more low-melting-point liquid phases. The low-melting-point liquid phases can promote ion migration and aggregation and rearrangement of raw material powder particles, and are helpful for the solid-phase sintering reaction between calcined talc, calcined kaolin and aluminum hydroxide. At the same time, the increase in liquid phase can also reduce the calcination temperature, which is beneficial to the sintering of cordierite phase, and finally form cordierite powder with a dense structure, which helps to reduce dielectric loss.
[0028] In addition, during the calcination process, V 5+ Entering the hexavalent channel of cordierite, new bonds VO-Si and VO are formed, replacing Al-O-Si and Mg-O bonds. 5+ The ionic radius of V is large, and the new bond formed will cause a certain degree of distortion of the six-membered channel, and finally form a proper amount of uniformly distributed micropores. These micropores can play a good role in expansion during the thermal expansion of cordierite powder. Therefore, when an appropriate amount of vanadium pentoxide is added, V 5+ The degree of distortion of the hexagonal ring is not large, and the pore size and the amount of micropores generated are moderate, thereby effectively reducing the thermal expansion coefficient of cordierite ceramics.
[0029] However, when the amount of vanadium pentoxide added exceeds the upper limit of the range specified in the present invention, the cordierite powder is severely deformed, resulting in larger gaps and more numerous cracks, holes and other defects inside the cordierite powder, resulting in the dielectric loss and thermal expansion coefficient of the cordierite powder increasing instead of decreasing. At the same time, a large number of defects will also affect the mechanical properties of the cordierite powder, ultimately resulting in a decrease in the flexural strength of the fired ceramic material.
[0030] In some optional examples, the ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass of the calcium fluoride is 1:(0.08~0.1), for example, it can be 1:0.08, 1:0.082, 1:0.084, 1:0.086, 1:0.088, 1:0.09, 1:0.092, 1:0.094, 1:0.096, 1:0.098 or 1:0.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the mass ratio of the cordierite precursor powder, abrasive balls and deionized water is 1:(1.3~1.6):(0.6~0.8), for example, it can be 1:1.3:0.6, 1:1.35:0.62, 1:1.4:0.64, 1:1.45:0.66, 1:1.5:0.68, 1:1.55:0.7, 1:1.6:0.72, 1:1.3:0.74, 1:1.4:0.76, 1:1.5:0.78, 1:1.6:0.8, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the rotation speed of the wet ball milling of the cordierite precursor powder, abrasive balls and deionized water is 250~300r / min, for example, it can be 250r / min, 255r / min, 260r / min, 265r / min, 270r / min, 275r / min, 280r / min, 285r / min, 290r / min, 295r / min or 300r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the wet ball milling time of the cordierite precursor powder, abrasive balls and deionized water is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the drying temperature of the cordierite precursor wet material is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the drying time of the cordierite precursor wet material is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] As a preferred technical solution of the present invention, the calcination process of the cordierite precursor dry material comprises the following steps:
[0037] First, the cordierite precursor dry material is heated to a first calcination temperature at a first heating rate, then continued to be heated to a second calcination temperature at a second heating rate, then continued to be heated to a third calcination temperature at a third heating rate, and kept warm at the third calcination temperature. After the insulation is completed, it is cooled to room temperature with the furnace, wherein the third heating rate is less than the first heating rate and less than the second heating rate.
[0038] In some optional instances, the first heating rate is 240~250℃ / h, for example, it can be 240℃ / h, 241℃ / h, 242℃ / h, 243℃ / h, 244℃ / h, 245℃ / h, 246℃ / h, 247℃ / h, 248℃ / h, 249℃ / h or 250℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the first calcination temperature is 290-300°C, for example, it can be 290°C, 291°C, 292°C, 293°C, 294°C, 295°C, 296°C, 297°C, 298°C, 299°C or 300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional instances, the second heating rate is 390~400℃ / h, for example, it can be 390℃, 391℃, 392℃, 393℃, 394℃, 395℃, 396℃, 397℃, 398℃, 399℃ or 400℃, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the second calcination temperature is 890-900°C, for example, it can be 890°C, 891°C, 892°C, 893°C, 894°C, 895°C, 896°C, 897°C, 898°C, 899°C or 900°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional instances, the third heating rate is 120~130℃ / h, for example, it can be 120℃ / h, 121℃ / h, 122℃ / h, 123℃ / h, 124℃ / h, 125℃ / h, 126℃ / h, 127℃ / h, 128℃ / h, 129℃ / h or 130℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the third calcination temperature is 1350-1360°C, for example, it can be 1350°C, 1351°C, 1352°C, 1353°C, 1354°C, 1355°C, 1356°C, 1357°C, 1358°C, 1359°C or 1360°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] During the calcination of the cordierite precursor dry material, as the calcination temperature increases, first, the free water and adsorbed water in the calcined talc, calcined kaolin and aluminum hydroxide are removed; then, the dehydrated calcined talc, calcined kaolin and aluminum hydroxide react to generate mullite, cristobalite, enstatite and α-alumina, and the mullite, cristobalite, enstatite and α-alumina react with each other and are continuously consumed to generate a small amount of the target product cordierite and the intermediate product magnesia-alumina spinel; finally, when the temperature reaches 1350~1360℃, the intermediate product magnesia-alumina spinel continues to react with cristobalite to generate cordierite, and after the insulation is completed, the sintering reaction is basically completed, and the intermediate products magnesia-alumina spinel and cristobalite are basically completely decomposed, and finally a cordierite powder with a higher purity is obtained.
[0045] The present invention specifically limits the third calcination temperature to 1350-1360°C. Since cordierite powder is a low melting point substance, too high a calcination temperature will cause part of the cordierite powder to volatilize, thereby causing the cordierite to lose weight. When the third calcination temperature exceeds 1360°C, although the purity of the cordierite powder obtained by calcination is high, the weight loss rate is also too high, and the yield is low; when the third calcination temperature is lower than 1350°C, although the weight loss rate of the cordierite powder is low, the intermediate products such as magnesium aluminum spinel and cristobalite cannot be decomposed and removed, and the purity of the fired cordierite powder is low; therefore, when the third calcination temperature is within the range of 1350-1360°C, cordierite powder with relatively high purity and relatively low weight loss rate can be obtained.
[0046] In some optional examples, the third calcination temperature is kept for 1.5 to 2.5 hours, for example, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the mesh size of the sieve used for screening is 150-200 mesh, for example, it can be 150 mesh, 155 mesh, 160 mesh, 165 mesh, 170 mesh, 175 mesh, 180 mesh, 185 mesh, 190 mesh or 200 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, the CBS powder is prepared by the following method:
[0049] Calcium carbonate, boric acid and silicon dioxide are uniformly mixed to obtain CBS precursor powder; the CBS precursor powder, grinding balls and anhydrous ethanol are mixed and wet-milled to obtain CBS precursor wet material; the CBS precursor wet material is dried to obtain CBS precursor dry material; the CBS precursor dry material is calcined, ground and sieved in sequence to obtain the CBS powder.
[0050] As a preferred technical solution of the present invention, the mass ratio of calcium carbonate, boric acid and silicon dioxide is (3~3.2):(2.8~3):1, for example, it can be 3:2.8:1, 3.02:2.82:1, 3.04:2.84:1, 3.06:2.86:1, 3.08:2.88:1, 3.1:2.9:1, 3.12:2.92:1, 3.14:2.94:1, 3.16:2.96:1, 3.18:2.98:1 or 3.2:3:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] CBS powder is a multiphase material composed of CaO, B2O3 and SiO2. Both B2O3 and SiO2 are network formers, but the network structures are different. They mainly play a role of skeleton support. Among them, B2O3 is a two-dimensional layered structure, mainly connected by [BO3]. When CaO is added, the free oxygen in the system increases and combines with [BO3] to form [BO4]. [BO4] can enhance the mechanical strength of CBS powder. SiO2 is a three-dimensional structure composed of [SiO4], and its dielectric loss is small. When CaO is added, the calcium ions in the system can react with Si-O to break the network, thereby changing the original network structure of the three-dimensional structure, making the particles easier to move. During the calcination process, it is beneficial to reduce the viscosity of the liquid phase and promote the sintering densification process of CBS powder.
[0052] During the sintering process of the ceramic powder, the CBS powder will undergo obvious crystallization, which will lead to an increase in the viscosity of the liquid phase. At the same time, since the firing temperature of the AlN material is high and the self-diffusion coefficient is low, the addition of AlN will further hinder the flow of the liquid phase, resulting in a higher viscosity of the liquid phase, which in turn causes the wettability of the liquid phase to the raw material powder particles to deteriorate, ultimately affecting the firing density of the ceramic material. Therefore, in order to make the ceramic material obtain a more compact crystal structure, the CBS powder used must have a lower melting point, so that a large amount of liquid phase can be generated during the sintering process of the ceramic powder, and the generated liquid phase should have a lower viscosity and good fluidity, so as to achieve a sufficient wetting effect on the powder particles. For this reason, the present invention adjusts the mass ratio of calcium carbonate, boric acid and silicon dioxide, limits the mass ratio of calcium carbonate, boric acid and silicon dioxide to within the range of (3~3.2): (2.8~3): 1, and then changes the composition ratio of CaO, B2O3 and SiO2, and obtains a CBS powder with a lower melting point and a lower high temperature viscosity, which ultimately achieves the purpose of improving the firing density of the ceramic material and reducing its dielectric loss.
[0053] The present invention specifically limits the mass ratio of calcium carbonate, boric acid and silicon dioxide to (3-3.2):(2.8-3):1. As the amount of calcium carbonate increases, the proportion of calcium oxide generated by the reaction increases, and the dielectric loss of CBS powder shows a trend of first rapidly decreasing and then slightly increasing. This is because the free oxygen ions (O 2- ) can be combined with the bridging oxygen (O 0 ) reaction, thereby destroying the Si-O network structure. The destroyed Si-O network structure is more likely to break at high temperatures, resulting in a decrease in the viscosity of the sintered system, thereby reducing the melting point of the CBS powder. Therefore, as the amount of calcium oxide generated gradually increases, the Si-O network structure in the CBS powder is more severely damaged, and the Si-O network structure breaks, resulting in a decrease in the melting point and high-temperature viscosity of the sintered CBS powder, thereby accelerating the sintering shrinkage of the CBS powder, and ultimately obtaining a CBS powder with a higher degree of densification. When the amount of calcium carbonate added exceeds the upper limit of the range defined in the present invention, the generated calcium oxide is excessive and is replaced by O 2- The severely damaged Si-O network structure is difficult to be further significantly damaged. Even if more calcium carbonate is added, the Si-O network structure in the CBS powder hardly changes. Therefore, the sintering shrinkage of the CBS powder at high temperature does not change significantly. However, with the increase in the proportion of calcium oxide, the crystallization temperature of the CBS powder will decrease, and the viscosity of the sintering system after crystallization will increase significantly, thereby preventing the densification process of the CBS powder. Therefore, excessive addition of calcium carbonate is not conducive to the densification process of the CBS powder, which in turn leads to a certain degree of increase in the dielectric loss of the CBS powder.
[0054] With the increase of the amount of boric acid, the proportion of boric oxide generated by the reaction increases, and the dielectric loss of CBS powder shows a trend of first decreasing and then increasing. This is because, compared with calcium oxide and silicon dioxide, boric oxide has a lower melting point. Adding an appropriate amount of boric acid to generate an appropriate amount of boric oxide can promote the viscous flow of CBS powder, thereby producing more liquid phase during the sintering process of CBS powder, so as to obtain a CBS powder with a denser structure; in addition, during the sintering process of CBS powder, the [BO3] group is inserted into the Si-O network structure, resulting in the destruction of the Si-O network structure of the CBS powder, thereby reducing the high-temperature viscosity of the sintering system, which is beneficial to accelerate the sintering densification process of CBS powder. Therefore, with the increase of the amount of boric oxide generated, the number of internal pores in the sintered CBS powder is significantly reduced, and the degree of densification is significantly improved. However, as the proportion of boron oxide continues to increase, the CaB2O4 crystal phase content in the fired CBS powder increases significantly, while the β-CaSiO3 crystal phase content decreases significantly. When the amount of boric acid reaches the upper limit of the range defined by the present invention, the main crystal phase of the fired CBS powder is CaB2O4. Compared with CaB2O4, β-CaSiO3 has a lower thermal expansion coefficient and lower dielectric loss. Therefore, when the content of β-CaSiO3 is too low, it will directly affect the dielectric properties and thermal properties of the CBS powder; but compared with CaB2O4, the softening temperature of β-CaSiO3 is higher. Therefore, the content of β-CaSiO3 cannot be too high, otherwise it will cause the liquid phase viscosity of the CBS powder to be too large, affecting the firing densification process of the ceramic material.
[0055] In some optional examples, the mass ratio of the CBS precursor powder, the abrasive balls and the anhydrous ethanol is 1:(3-4):(1.5-2.5), for example, it can be 1:3:1.5, 1:3.1:1.6, 1:3.2:1.7, 1:3.3:1.8, 1:3.4:1.9, 1:3.5:2, 1:3.6:2.1, 1:3.7:2.2, 1:3.8:2.3, 1:3.9:2.4 or 1:4:2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0056] In some optional examples, the rotation speed of the wet ball milling of the CBS precursor powder, grinding balls and anhydrous ethanol is 280-320 r / min, for example, it can be 280 r / min, 285 r / min, 290 r / min, 295 r / min, 300 r / min, 305 r / min, 310 r / min, 315 r / min or 320 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0057] In some optional examples, the wet ball milling time of the CBS precursor powder, grinding balls and anhydrous ethanol is 1.5 to 2.5 hours, for example, it can be 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0058] In some optional examples, the drying temperature of the CBS precursor wet material is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the drying time of the CBS precursor wet material is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] As a preferred technical solution of the present invention, the calcination process of the CBS precursor dry material comprises the following steps:
[0061] First, the CBS precursor dry material is heated to a fourth calcination temperature at a fourth heating rate and kept warm, then continued to be heated to a fifth calcination temperature at a fifth heating rate and kept warm, and finally cooled to a sixth calcination temperature at a first cooling rate and kept warm, and after the insulation is completed, cooled to room temperature with the furnace, wherein the first cooling rate is less than the fourth heating rate and less than the fifth heating rate.
[0062] In some optional instances, the fourth heating rate is 120~130℃ / h, for example, it can be 120℃ / h, 121℃ / h, 122℃ / h, 123℃ / h, 124℃ / h, 125℃ / h, 126℃ / h, 127℃ / h, 128℃ / h, 129℃ / h or 130℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the fourth calcination temperature is 450-460°C, for example, it can be 450°C, 451°C, 452°C, 453°C, 454°C, 455°C, 456°C, 457°C, 458°C, 459°C or 460°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the fourth calcination temperature is kept for 1.8 to 2.2 hours, for example, 1.8 hours, 1.85 hours, 1.9 hours, 1.95 hours, 2.0 hours, 2.05 hours, 2.1 hours, 2.15 hours or 2.2 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional instances, the fifth heating rate is 590~600℃ / h, for example, it can be 590℃ / h, 591℃ / h, 592℃ / h, 593℃ / h, 594℃ / h, 595℃ / h, 596℃ / h, 597℃ / h, 598℃ / h, 599℃ / h or 600℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional examples, the fifth calcination temperature is 960-970°C, for example, it can be 960°C, 961°C, 962°C, 963°C, 964°C, 965°C, 966°C, 967°C, 968°C, 969°C or 970°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] In some optional examples, the fifth calcination temperature is kept for 1.8 to 2.2 hours, for example, 1.8 hours, 1.85 hours, 1.9 hours, 1.95 hours, 2.0 hours, 2.05 hours, 2.1 hours, 2.15 hours or 2.2 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional instances, the first cooling rate is 80~90℃ / h, for example, it can be 80℃ / h, 81℃ / h, 82℃ / h, 83℃ / h, 84℃ / h, 85℃ / h, 86℃ / h, 87℃ / h, 88℃ / h, 89℃ / h or 90℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the sixth calcination temperature is 620-630°C, for example, it can be 620°C, 621°C, 622°C, 623°C, 624°C, 625°C, 626°C, 627°C, 628°C, 629°C or 630°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some optional examples, the sixth calcination temperature is kept for 0.5 to 1.5 hours, for example, 0.5 hours, 0.6 hours, 0.7 hours, 0.8 hours, 0.9 hours, 1.0 hours, 1.1 hours, 1.2 hours, 1.3 hours, 1.4 hours or 1.5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] The CBS precursor dry material defined in the present invention adopts a two-stage calcination process, specifically, the furnace temperature is used as the initial temperature, the temperature is first raised to 450-460° C., and the temperature is kept for 1.8-2.2 hours. This stage is to fully volatilize the moisture and organic matter in the CBS precursor dry material. In order to ensure the full volatilization of the moisture and organic matter, the heating rate in this stage must be slow enough. Therefore, the present invention limits the heating rate in this stage to 120-130° C. / h. Subsequently, the temperature is increased from 450-460°C to a sintering temperature of 960-970°C. The present invention specifically limits the heating rate in this stage to 590-600°C / h. If the heating rate is lower than 590°C / h, CBS has sufficient time to form crystal nuclei during the calcination process, resulting in coarse grains of the CBS powder obtained by calcination. On the one hand, the coarse grains reduce the total length of the grain boundaries, thereby reducing the resistance of the CBS powder to dislocation movement. At the same time, the coarse grains easily lead to uneven stress distribution inside the CBS powder, resulting in stress concentration areas, and ultimately resulting in reduced mechanical properties of the sintered CBS powder. On the other hand, the coarse grains mean a reduction in the number of grain boundaries, which are defective areas inside the CBS powder and have a higher energy state. Under the action of the alternating electric field, the migration and accumulation of charges at the grain boundaries will lead to energy loss. Therefore, the reduction in the number of grain boundaries will reduce the efficiency of charge migration and accumulation, thereby increasing the dielectric loss of the CBS powder. When the heating rate is higher than 600℃ / h, the CBS powder will reach the crystallization temperature before the densification is completed, which will affect the growth of the grains and make the structure of the sintered CBS powder loose, which will also lead to an increase in the dielectric loss of the CBS powder.
[0072] In some optional examples, the mesh size of the sieve used for screening is 150-200 mesh, for example, it can be 150 mesh, 155 mesh, 160 mesh, 165 mesh, 170 mesh, 175 mesh, 180 mesh, 185 mesh, 190 mesh or 200 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] As a preferred technical solution of the present invention, the mass fraction of aluminum oxide in the precursor mixture is 40~50wt%, for example, it can be 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt% or 50wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the mass fraction of aluminum nitride in the precursor mixture is 30-40wt%, for example, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In some optional examples, the mass fraction of cordierite powder in the precursor mixture is 9~10wt%, for example, it can be 9.0wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt% or 10.0wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] The addition of cordierite powder will reduce the sintering temperature of the ceramic material, and with the increase of the amount of cordierite powder added, the decrease in sintering temperature will gradually increase. The reason is that during the sintering process, part of the cordierite powder decomposes or volatilizes, releasing a large amount of energy, which promotes sintering densification. However, when the amount of cordierite powder added exceeds 10wt%, it will also have an adverse effect on the mechanical properties and thermal properties of the calcined ceramic material. This is because when the cordierite powder is added in excess, it promotes the reaction of Al2O3 and AlN to generate Al5O6N impurity phase. The Al5O6N phase is dispersed at the grain boundary of the Al2O3+AlN solid solution, which will lead to a decrease in the mechanical strength of the ceramic material and an increase in the thermal expansion coefficient.
[0077] In some optional examples, the mass fraction of CBS powder in the precursor mixture is 3.8-4.2wt%, for example, 3.8wt%, 3.85wt%, 3.9wt%, 3.95wt%, 4.0wt%, 4.05wt%, 4.1wt%, 4.15wt% or 4.2wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] CBS powder improves the performance of ceramic materials through the liquid phase sintering mechanism. CBS powder forms a low melting point glass phase at high temperature. During sintering, the glass phase with a lower melting point will turn into a liquid phase, which helps to promote the melting, aggregation and bonding between the raw powder particles, so that the grains are rearranged during the sintering process, the contact is strengthened, and the grain boundary mobility is improved, thereby achieving the densification of the ceramic material at a lower sintering temperature.
[0079] When the mass fraction of CBS powder is between 3.8 and 4.2 wt%, a large amount of liquid phase can be formed in the sintering system. A large amount of liquid phase infiltrates into the three-dimensional mesh structure formed by the raw material powder particles, fully wetting and wrapping the raw material powder particles, making the structure of the fired ceramic material more compact and significantly reducing the dielectric loss. When the mass fraction of CBS powder is lower than 3.8 wt%, the amount of liquid phase generated is small, and the surface of the raw material powder particles cannot be fully wetted and wrapped by the liquid phase, which ultimately leads to a decrease in the structural density of the fired ceramic material and an increase in the dielectric loss. When the mass fraction of CBS powder exceeds 4.2 wt%, cristobalite will precipitate in the sintering system. With the continuous precipitation of cristobalite, the glass phase decreases, the liquid phase sintering effect weakens, and the surface of a large number of raw material powder particles cannot be fully wetted and wrapped by a small amount of molten liquid phase, which also leads to a decrease in the structural density of the ceramic material and an increase in the dielectric loss.
[0080] In some optional examples, the rare earth oxides consist of yttrium oxide, cerium oxide and lanthanum oxide.
[0081] In some optional instances, the mass fraction of yttrium oxide in the precursor mixture is 2.4~2.6wt%, for example, it can be 2.4wt%, 2.42wt%, 2.44wt%, 2.46wt%, 2.48wt%, 2.5wt%, 2.52wt%, 2.54wt%, 2.56wt%, 2.58wt% or 2.6wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In some optional examples, the mass fraction of cerium oxide in the precursor mixture is 0.4~0.6wt%, for example, it can be 0.4wt%, 0.42wt%, 0.44wt%, 0.46wt%, 0.48wt%, 0.5wt%, 0.52wt%, 0.54wt%, 0.56wt%, 0.58wt% or 0.6wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] In some optional examples, the mass fraction of lanthanum oxide in the precursor mixture is 2.4~2.6wt%, for example, it can be 2.4wt%, 2.42wt%, 2.44wt%, 2.46wt%, 2.48wt%, 2.5wt%, 2.52wt%, 2.54wt%, 2.56wt%, 2.58wt% or 2.6wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] The present invention specifically limits the mass fraction of yttrium oxide, cerium oxide and lanthanum oxide in the precursor mixture. When the addition amount of yttrium oxide, cerium oxide and lanthanum oxide is within this numerical range, the obtained ceramic material has excellent dielectric properties. This is because adding an appropriate amount of rare earth oxide can effectively inhibit grain growth, refine grains, and increase the amount of liquid phase at the same time, prompting the liquid phase to fully fill the gaps between the raw material powder particles, so that the density of the ceramic material is improved and the mechanical properties are enhanced. However, when the addition amount of rare earth oxide exceeds the upper limit of the range defined by the present invention, the grain size of the ceramic material will increase again. This is because adding excessive rare earth oxide will greatly increase the amount of liquid phase generated, significantly reduce the viscosity of the liquid phase, and improve the ion mobility, resulting in excessive growth of grains, larger grain size, and more gaps, which ultimately leads to a decrease in the density of the ceramic material and an increase in dielectric loss.
[0085] In some optional examples, the mass ratio of the precursor mixture, the abrasive balls and the deionized water is 1:(1.8~2):(0.5~0.6), for example, it can be 1:1.8:0.5, 1:1.82:0.51, 1:1.84:0.52, 1:1.86:0.53, 1:1.88:0.54, 1:1.9:0.55, 1:1.92:0.56, 1:1.94:0.57, 1:1.96:0.58, 1:1.98:0.59 or 1:2:0.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some optional examples, the rotation speed of wet ball milling of the precursor mixture, abrasive balls and deionized water is 300~350r / min, for example, it can be 300r / min, 305r / min, 310r / min, 315r / min, 320r / min, 325r / min, 330r / min, 335r / min, 340r / min, 345r / min or 350r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] In some optional examples, the wet ball milling time of the precursor mixture, abrasive balls and deionized water is 1.5 to 2.5 hours, for example, it can be 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] In some optional examples, the drying temperature of the precursor wet material is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0089] In some optional examples, the drying time of the precursor wet material is 8 to 12 hours, for example, it can be 8.0 hours, 8.5 hours, 9.0 hours, 9.5 hours, 10.0 hours, 10.5 hours, 11.0 hours, 11.5 hours or 12.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] In some optional examples, the mesh number of the sieve through which the precursor wet material is sieved after drying is 150-160 mesh, for example, it can be 150 mesh, 151 mesh, 152 mesh, 153 mesh, 154 mesh, 155 mesh, 156 mesh, 157 mesh, 158 mesh, 159 mesh or 160 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] In some optional examples, the polyvinyl butyral solution consists of polyvinyl butyral and anhydrous ethanol.
[0092] In some optional examples, the concentration of polyvinyl butyral in the polyvinyl butyral solution is 35-45 g / L, for example, 35 g / L, 36 g / L, 37 g / L, 38 g / L, 39 g / L, 40 g / L, 41 g / L, 42 g / L, 43 g / L, 44 g / L or 45 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In some optional examples, the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:(0.08~0.1), for example, it can be 1:0.08, 1:0.082, 1:0.084, 1:0.086, 1:0.088, 1:0.09, 1:0.092, 1:0.094, 1:0.096, 1:0.098 or 1:0.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] In some optional embodiments, the inlet temperature of the spray granulation of the precursor solution is 250-260°C, for example, it can be 250°C, 251°C, 252°C, 253°C, 254°C, 255°C, 256°C, 257°C, 258°C, 259°C or 260°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] In some optional examples, the outlet temperature of the spray granulation of the precursor solution is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0096] In some optional examples, the feed flow rate of the spray granulation of the precursor solution is 25~30mL / min, for example, it can be 25mL / min, 25.5mL / min, 26mL / min, 26.5mL / min, 27mL / min, 27.5mL / min, 28mL / min, 28.5mL / min, 29mL / min, 29.5mL / min or 30mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0097] In some optional examples, the tableting pressure of the precursor powder is 35~45MPa, for example, it can be 35MPa, 36MPa, 37MPa, 38MPa, 39MPa, 40MPa, 41MPa, 42MPa, 43MPa, 44MPa or 45MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] In some optional examples, the tableting time of the precursor powder is 5 to 15 seconds, for example, it can be 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds or 15 seconds, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0099] As a preferred technical solution of the present invention, the heating rate of the blank to the debinding temperature is 110-130°C / h, for example, it can be 110°C / h, 112°C / h, 114°C / h, 116°C / h, 118°C / h, 120°C / h, 122°C / h, 124°C / h, 126°C / h, 128°C / h or 130°C / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0100] In some optional instances, the debinding temperature is 650-660°C, for example, it can be 650°C, 651°C, 652°C, 653°C, 654°C, 655°C, 656°C, 657°C, 658°C, 659°C or 660°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0101] The debinding process needs to be carried out in a hot atmosphere with sufficient oxygen so that polyvinyl butyral (PVB) can fully react to generate CO2. If oxygen is scarce, PVB will not burn completely, resulting in a large amount of residual carbon in the fired ceramic material. However, since aluminum nitride is easily oxidized, the debinding temperature should not exceed 660°C to prevent aluminum nitride from being oxidized during the debinding process. However, when the debinding temperature is lower than 650°C, the sintering temperature is too low to form a certain chemical bond inside the material, resulting in a low bonding strength inside the material after debinding.
[0102] In some optional examples, the holding time at the debinding temperature is 2.5 to 3.5 hours, for example, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours, 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours or 3.5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In some optional instances, the heating rate from the debinding temperature to the first sintering temperature is 240~250℃ / h, for example, it can be 240℃ / h, 241℃ / h, 242℃ / h, 243℃ / h, 244℃ / h, 245℃ / h, 246℃ / h, 247℃ / h, 248℃ / h, 249℃ / h or 250℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0104] The present invention specifically limits the heating rate from the debinding temperature to the first sintering temperature to 240-250°C / h. When the heating rate is lower than 240°C / h, the nucleation time of the ceramic material is too long, so that the ceramic material is accompanied by a large amount of crystallization during the densification process, resulting in coarse grains of the fired ceramic material. On the one hand, the coarse grains reduce the total length of the grain boundaries, thereby reducing the resistance of the ceramic material to dislocation movement. At the same time, the coarse grains easily lead to uneven stress distribution inside the ceramic material, resulting in stress concentration areas, and ultimately leading to reduced mechanical properties of the fired ceramic material. On the other hand, the coarse grains mean a reduction in the number of grain boundaries, and the grain boundaries are defective areas inside the ceramic material with a higher energy state. Under the action of the alternating electric field, the migration and accumulation of charges at the grain boundaries will lead to energy loss. Therefore, the reduction in the number of grain boundaries will reduce the migration and accumulation efficiency of the charges, thereby leading to an increase in the dielectric loss of the ceramic material. When the heating rate is higher than 600℃ / h, the ceramic material will reach the crystallization temperature before densification is completed, which will affect the growth of grains. The structure of the calcined ceramic material will be loose, which will also increase the dielectric loss of the ceramic material.
[0105] In some optional instances, the first sintering temperature is 1500~1550℃, for example, it can be 1500℃, 1505℃, 1510℃, 1515℃, 1520℃, 1525℃, 1530℃, 1535℃, 1540℃, 1545℃ or 1550℃, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0106] In some optional instances, the holding time at the first sintering temperature is 15 to 25 minutes, for example, it can be 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes or 25 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0107] In some optional instances, the cooling rate from the first sintering temperature to the second sintering temperature is 290~300℃ / h, for example, it can be 290℃ / h, 291℃ / h, 292℃ / h, 293℃ / h, 294℃ / h, 295℃ / h, 296℃ / h, 297℃ / h, 298℃ / h, 299℃ / h or 300℃ / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0108] In some optional instances, the second sintering temperature is 1350-1360°C, for example, it may be 1350°C, 1351°C, 1352°C, 1353°C, 1354°C, 1355°C, 1356°C, 1357°C, 1358°C, 1359°C or 1360°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0109] In some optional examples, the holding time at the second sintering temperature is 7 to 8 hours, for example, it can be 7.0h, 7.1h, 7.2h, 7.3h, 7.4h, 7.5h, 7.6h, 7.7h, 7.8h, 7.9h or 8.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0110] The present invention specifically limits the holding time at the second sintering temperature to 7 to 8 hours. When the holding time is less than 7 hours, the bubbles inside the ceramic material cannot be fully discharged during the holding process, resulting in poor density of the fired ceramic material and increased dielectric loss. As the holding time increases, the bubbles inside the ceramic material are completely discharged, the pores inside the fired ceramic material are significantly reduced, the grain size increases, the crystal structure becomes denser, and the dielectric loss is significantly reduced. When the holding time exceeds 8 hours, the grains of the ceramic material have sufficient time to grow, which leads to uneven grain size and relatively coarse grains. On the one hand, it is easy to cause uneven stress distribution inside the ceramic material, produce stress concentration areas, and ultimately lead to reduced mechanical properties of the fired ceramic material; on the other hand, coarse grains mean a reduction in the number of grain boundaries, and the reduction in the number of grain boundaries reduces the efficiency of charge migration and accumulation, thereby increasing the dielectric loss of the ceramic material.
[0111] In some optional examples, the furnace temperature is 90~100℃, for example, it can be 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃ or 100℃, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0112] In a second aspect, the present invention provides a low dielectric loss tangent ceramic material for system-level packaging prepared by the preparation method described in the first aspect.
[0113] Compared with the prior art, the present invention has the following beneficial effects:
[0114] Ceramic materials for packaging need to have the characteristics of low dielectric loss, high flexural strength and low thermal expansion coefficient. Alumina has the characteristics of good dielectric properties, high flexural strength and good chemical corrosion resistance. Aluminum nitride has the characteristics of low dielectric loss, low thermal expansion coefficient, high insulation resistance and high thermal conductivity. The present invention uses alumina and aluminum nitride as the main ceramic raw materials for ceramic materials for packaging. By adding cordierite powder, CBS powder and rare earth oxides to the ceramic raw materials, the sintering temperature of the ceramic material is greatly reduced. A ceramic material with a dense structure can be formed at a relatively low sintering temperature, and finally an Al2O3 / AlN composite ceramic material with ideal dielectric properties, mechanical properties and thermal properties is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0115] Figure 1 A flow chart of a method for preparing a low dielectric loss tangent ceramic material for system-level packaging provided in Examples 1-5 of the present invention;
[0116] Figure 2 The XRD spectra of the cordierite powders prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown;
[0117] Figure 3 This is a scanning electron microscope image of the cordierite powder prepared in Example 1 of the present invention;
[0118] Figure 4 This is a scanning electron microscope image of the cordierite powder prepared in Comparative Example 2 of the present invention;
[0119] Figure 5 This is a scanning electron microscope image of the CBS powder prepared in Comparative Example 5 of the present invention;
[0120] Figure 6 This is a scanning electron microscope image of the CBS powder prepared in Example 1 of the present invention;
[0121] Figure 7 This is a scanning electron microscope image of the CBS powder prepared in Comparative Example 6 of the present invention;
[0122] Figure 8 This is a scanning electron microscope image of the ceramic material prepared in Example 1 of the present invention;
[0123] Fig. 9 This is a scanning electron microscope image of the ceramic material prepared in Comparative Example 9 of the present invention;
[0124] Fig.10 This is a scanning electron microscope image of the ceramic material prepared in Comparative Example 10 of the present invention. DETAILED DESCRIPTION
[0125] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0126] The chemical reagents used in the examples are all commercially available products, and their specifications, models, manufacturers and other information are as follows:
[0127] Talc: S30618-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0128] Kaolin: S30588-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0129] Aluminum hydroxide: S30353-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0130] Vanadium pentoxide: purity ≥99%, purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0131] Calcium fluoride: S50691-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0132] Calcium carbonate: S24297-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0133] Boric acid: purity ≥99.5%, purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd.
[0134] Silica: S30499-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0135] Alumina: S41887-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0136] Aluminum nitride: S44988-250g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0137] Yttrium oxide: S24438-10g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0138] Cerium oxide: S41912-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0139] Lanthanum oxide: S24341-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0140] Polyvinyl butyral: S30198-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0141] Example 1
[0142] This embodiment provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0143] (1) heating the talc particles to 1000°C and keeping the temperature for 5 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding and sieving the calcined talc particles to obtain calcined talc with a particle size D90 of 18 μm;
[0144] (2) heating the kaolin particles to 900°C and keeping the temperature for 2 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding and sieving the calcined kaolin particles to obtain calcined kaolin with a particle size D90 of 2 μm;
[0145] (3) the calcined talc obtained in step (1), the calcined kaolin obtained in step (2), aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain a cordierite precursor powder, wherein the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is 37:48:19, the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass ratio of vanadium pentoxide is 1:0.03, and the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to calcium fluoride is 1:0.08;
[0146] (4) The cordierite precursor powder prepared in step (3), abrasive balls and deionized water were mixed in a mass ratio of 1:1.3:0.6, and wet-milled at a speed of 250 r / min for 3 h to obtain a cordierite precursor wet material; the cordierite precursor wet material was dried at 70° C. for 3 h to obtain a cordierite precursor dry material; the cordierite precursor dry material was calcined, ground and sieved through a 150-mesh sieve in sequence to obtain a cordierite powder;
[0147] The calcination process of the cordierite precursor dry material includes the following steps:
[0148] First, the cordierite precursor dry material was heated to 290°C at a heating rate of 240°C / h, then continued to be heated to 890°C at a heating rate of 390°C / h, then continued to be heated to 1350°C at a heating rate of 120°C / h and kept at this temperature for 2.5h, and then cooled to room temperature with the furnace after the end of the heat preservation;
[0149] (5) Calcium carbonate, boric acid and silicon dioxide are mixed uniformly in a mass ratio of 3:2.8:1 to obtain CBS precursor powder; CBS precursor powder, grinding balls and anhydrous ethanol are mixed in a mass ratio of 1:3:1.5, and wet-milled at a speed of 280 r / min for 2.5 hours to obtain CBS precursor wet material; the CBS precursor wet material is dried at 70° C. for 3 hours to obtain CBS precursor dry material; the CBS precursor dry material is calcined, ground and sieved through a 150-mesh sieve in sequence to obtain CBS powder;
[0150] The calcination process of the CBS precursor dry material includes the following steps:
[0151] First, the CBS precursor dry material was heated to 450°C at a heating rate of 120°C / h and kept at this temperature for 2.2h, then continued to be heated to 960°C at a heating rate of 590°C / h and kept at this temperature for 2.2h, and finally cooled to 620°C at a cooling rate of 80°C / h and kept at this temperature for 1.5h. After the end of the holding period, it was cooled to room temperature in the furnace.
[0152] (6) mixing aluminum oxide, aluminum nitride, the cordierite powder obtained in step (4), the CBS powder obtained in step (5), yttrium oxide, cerium oxide and lanthanum oxide uniformly to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 40wt%, the mass fraction of aluminum nitride is 40wt%, the mass fraction of cordierite powder is 10wt%, the mass fraction of CBS powder is 4.2wt%, the mass fraction of yttrium oxide is 2.6wt%, the mass fraction of cerium oxide is 0.6wt%, and the mass fraction of lanthanum oxide is 2.6wt%;
[0153] The precursor mixture, abrasive balls and deionized water prepared above were mixed in a mass ratio of 1:1.8:0.5, and wet-milled at a speed of 300 r / min for 2.5 hours to obtain a precursor wet material; the precursor wet material was dried at 80° C. for 12 hours, and then crushed and ground, and after grinding, passed through a 150-mesh sieve to obtain a precursor dry powder;
[0154] (7) mixing the precursor dry powder obtained in step (6) with 35 g / L polyvinyl butyral solution to obtain a precursor solution, wherein the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:0.08;
[0155] The precursor solution prepared above was subjected to spray granulation to obtain precursor powder, wherein the inlet temperature of the spray granulation was 250° C., the outlet temperature was 100° C., and the feed flow rate was 25 mL / min; the precursor powder was placed in a mold, and tableted at 35 MPa for 15 seconds to obtain a green body;
[0156] (8) calcining the green body obtained in step (7), the specific steps comprising:
[0157] The green body is heated to 650°C at a heating rate of 110°C / h and kept at this temperature for 3.5 hours, then continued to be heated to 1500°C at a heating rate of 240°C / h and kept at this temperature for 25 minutes, then cooled to 1350°C at a cooling rate of 290°C / h and kept at this temperature for 8 hours. After the insulation is completed, it is cooled to 90°C in the furnace and then taken out, and cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material.
[0158] Example 2
[0159] This embodiment provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0160] (1) heating talc particles to 1050° C. and keeping the temperature for 4.5 h, cooling to room temperature with the furnace to complete calcination, crushing, grinding and sieving the calcined talc particles to obtain calcined talc with a particle size D90 of 18.5 μm;
[0161] (2) heating the kaolin particles to 920° C. and keeping the temperature for 1.8 h, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding, and sieving the calcined kaolin particles to obtain calcined kaolin with a particle size D90 of 2.2 μm;
[0162] (3) the calcined talc obtained in step (1), the calcined kaolin obtained in step (2), aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain a cordierite precursor powder, wherein the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is 37.2:48.2:19.2, the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass ratio of vanadium pentoxide is 1:0.035, and the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to calcium fluoride is 1:0.085;
[0163] (4) The cordierite precursor powder prepared in step (3), abrasive balls and deionized water were mixed in a mass ratio of 1:1.4:0.65, and wet-milled at a speed of 260 r / min for 2.8 h to obtain a cordierite precursor wet material; the cordierite precursor wet material was dried at 72° C. for 2.8 h to obtain a cordierite precursor dry material; the cordierite precursor dry material was calcined, ground and sieved through a 160-mesh sieve in sequence to obtain a cordierite powder;
[0164] The calcination process of the cordierite precursor dry material includes the following steps:
[0165] First, the cordierite precursor dry material was heated to 292°C at a heating rate of 242°C / h, then continued to be heated to 892°C at a heating rate of 392°C / h, then continued to be heated to 1352°C at a heating rate of 122°C / h and kept at this temperature for 2.2h, and then cooled to room temperature with the furnace after the end of the heat preservation;
[0166] (5) Calcium carbonate, boric acid and silicon dioxide were mixed uniformly in a mass ratio of 3.05:2.85:1 to obtain CBS precursor powder; CBS precursor powder, grinding balls and anhydrous ethanol were mixed in a mass ratio of 1:3.2:1.8, and wet-milled at a speed of 290 r / min for 2.2 h to obtain CBS precursor wet material; the CBS precursor wet material was dried at 72° C. for 2.8 h to obtain CBS precursor dry material; the CBS precursor dry material was calcined, ground and sieved through a 160-mesh sieve in sequence to obtain CBS powder;
[0167] The calcination process of the CBS precursor dry material includes the following steps:
[0168] First, the CBS precursor dry material was heated to 452°C at a heating rate of 122°C / h and kept at this temperature for 2.1h, then continued to be heated to 962°C at a heating rate of 592°C / h and kept at this temperature for 2.1h, and finally cooled to 622°C at a cooling rate of 82°C / h and kept at this temperature for 1.2h. After the end of the holding period, it was cooled to room temperature in the furnace.
[0169] (6) mixing aluminum oxide, aluminum nitride, the cordierite powder obtained in step (4), the CBS powder obtained in step (5), yttrium oxide, cerium oxide and lanthanum oxide uniformly to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 43wt%, the mass fraction of aluminum nitride is 38.6wt%, the mass fraction of cordierite powder is 9wt%, the mass fraction of CBS powder is 3.8wt%, the mass fraction of yttrium oxide is 2.6wt%, the mass fraction of cerium oxide is 0.4wt%, and the mass fraction of lanthanum oxide is 2.6wt%;
[0170] The precursor mixture, abrasive balls and deionized water prepared above were mixed in a mass ratio of 1:1.85:0.52, and wet ball milled at a speed of 310 r / min for 2.2 h to obtain a precursor wet material; the precursor wet material was dried at 82° C. for 11 h, and then crushed and ground, and after grinding, passed through a 152 mesh sieve to obtain a precursor dry powder;
[0171] (7) mixing the precursor dry powder obtained in step (6) with 38 g / L polyvinyl butyral solution to obtain a precursor solution, wherein the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:0.085;
[0172] The precursor solution prepared above was subjected to spray granulation to obtain precursor powder, wherein the inlet temperature of the spray granulation was 252° C., the outlet temperature was 105° C., and the feed flow rate was 26 mL / min; the precursor powder was placed in a mold, and tabletted at 38 MPa for 12 seconds to obtain a green body;
[0173] (8) calcining the green body obtained in step (7), the specific steps comprising:
[0174] The green body is heated to 652°C at a heating rate of 115°C / h and kept at this temperature for 3.2h, then continued to be heated to 1510°C at a heating rate of 242°C / h and kept at this temperature for 22min, then cooled to 1352°C at a cooling rate of 292°C / h and kept at this temperature for 7.8h. After the insulation is completed, it is cooled to 92°C in the furnace and taken out, and cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material.
[0175] Example 3
[0176] This embodiment provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0177] (1) heating the talc particles to 1100° C. and keeping the temperature for 4 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding and sieving the calcined talc particles to obtain calcined talc with a particle size D90 of 19 μm;
[0178] (2) heating the kaolin particles to 950°C and keeping the temperature for 1.5 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding, and sieving the calcined kaolin particles to obtain calcined kaolin with a particle size D90 of 2.5 μm;
[0179] (3) the calcined talc obtained in step (1), the calcined kaolin obtained in step (2), aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain a cordierite precursor powder, wherein the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is 37.5:48.5:19.5, the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass ratio of vanadium pentoxide is 1:0.04, and the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to calcium fluoride is 1:0.09;
[0180] (4) mixing the cordierite precursor powder prepared in step (3), abrasive balls and deionized water in a mass ratio of 1:1.5:0.7, and wet-milling the mixture at a speed of 280 r / min for 2.5 h to obtain a cordierite precursor wet material; drying the cordierite precursor wet material at 75° C. for 2.5 h to obtain a cordierite precursor dry material; and calcining, grinding and sieving the cordierite precursor dry material in sequence to obtain cordierite powder;
[0181] The calcination process of the cordierite precursor dry material includes the following steps:
[0182] First, the cordierite precursor dry material was heated to 295°C at a heating rate of 245°C / h, then continued to be heated to 895°C at a heating rate of 395°C / h, then continued to be heated to 1355°C at a heating rate of 125°C / h and kept at this temperature for 2h, and then cooled to room temperature with the furnace after the end of the heat preservation;
[0183] (5) Calcium carbonate, boric acid and silicon dioxide were mixed in a mass ratio of 3.1:2.9:1 to obtain CBS precursor powder; CBS precursor powder, grinding balls and anhydrous ethanol were mixed in a mass ratio of 1:3.5:2, and wet-milled at a speed of 300 r / min for 2 h to obtain CBS precursor wet material; the CBS precursor wet material was dried at 75°C for 2.5 h to obtain CBS precursor dry material; the CBS precursor dry material was calcined, ground and sieved through a 170-mesh sieve in sequence to obtain CBS powder;
[0184] The calcination process of the CBS precursor dry material includes the following steps:
[0185] First, the CBS precursor dry material was heated to 455°C at a heating rate of 125°C / h and kept at this temperature for 2h, then continued to be heated to 965°C at a heating rate of 595°C / h and kept at this temperature for 2h, and finally cooled to 625°C at a cooling rate of 85°C / h and kept at this temperature for 1h, and then cooled to room temperature with the furnace after the end of the holding period;
[0186] (6) mixing aluminum oxide, aluminum nitride, the cordierite powder obtained in step (4), the CBS powder obtained in step (5), yttrium oxide, cerium oxide and lanthanum oxide uniformly to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 45wt%, the mass fraction of aluminum nitride is 35.5wt%, the mass fraction of cordierite powder is 10wt%, the mass fraction of CBS powder is 4wt%, the mass fraction of yttrium oxide is 2.6wt%, the mass fraction of cerium oxide is 0.5wt%, and the mass fraction of lanthanum oxide is 2.4wt%;
[0187] The precursor mixture, abrasive balls and deionized water prepared above were mixed in a mass ratio of 1:1.9:0.55, and wet ball milled at a speed of 320 r / min for 2 h to obtain a precursor wet material; the precursor wet material was dried at 85° C. for 10 h, and then crushed and ground, and after grinding, passed through a 155 mesh sieve to obtain a precursor dry powder;
[0188] (7) mixing the precursor dry powder obtained in step (6) with 40 g / L polyvinyl butyral solution to obtain a precursor solution, wherein the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:0.09;
[0189] The precursor solution prepared above was subjected to spray granulation to obtain precursor powder, wherein the inlet temperature of the spray granulation was 255° C., the outlet temperature was 110° C., and the feed flow rate was 27 mL / min; the precursor powder was placed in a mold, and tabletted at 40 MPa for 10 seconds to obtain a green body;
[0190] (8) calcining the green body obtained in step (7), the specific steps comprising:
[0191] The green body is heated to 655°C at a heating rate of 120°C / h and kept at this temperature for 3 hours, then continued to be heated to 1520°C at a heating rate of 245°C / h and kept at this temperature for 20 minutes, then cooled to 1355°C at a cooling rate of 295°C / h and kept at this temperature for 7.5 hours. After the insulation is completed, it is cooled to 95°C in the furnace and then taken out, and cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material.
[0192] Example 4
[0193] This embodiment provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0194] (1) heating talc particles to 1150° C. and keeping the temperature for 3.5 hours, cooling to room temperature with the furnace to complete calcination, crushing, grinding and sieving the calcined talc particles to obtain calcined talc with a particle size D90 of 19.5 μm;
[0195] (2) heating the kaolin particles to 980°C and keeping the temperature for 1.2 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding, and sieving the calcined kaolin particles to obtain calcined kaolin with a particle size D90 of 2.8 μm;
[0196] (3) the calcined talc obtained in step (1), the calcined kaolin obtained in step (2), aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain a cordierite precursor powder, wherein the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is 37.8:48.8:19.8, the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass ratio of vanadium pentoxide is 1:0.045, and the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to calcium fluoride is 1:0.095;
[0197] (4) The cordierite precursor powder prepared in step (3), abrasive balls and deionized water were mixed in a mass ratio of 1:1.5:0.75, and wet-milled at a speed of 290 r / min for 2.2 h to obtain a cordierite precursor wet material; the cordierite precursor wet material was dried at 78° C. for 2.2 h to obtain a cordierite precursor dry material; the cordierite precursor dry material was calcined, ground and sieved through a 180-mesh sieve in sequence to obtain a cordierite powder;
[0198] The calcination process of the cordierite precursor dry material includes the following steps:
[0199] First, the cordierite precursor dry material was heated to 298°C at a heating rate of 248°C / h, then continued to be heated to 898°C at a heating rate of 398°C / h, then continued to be heated to 1358°C at a heating rate of 128°C / h and kept at this temperature for 1.8h, and then cooled to room temperature with the furnace after the end of the heat preservation;
[0200] (5) Calcium carbonate, boric acid and silicon dioxide were mixed in a mass ratio of 3.15:2.95:1 to obtain CBS precursor powder; CBS precursor powder, grinding balls and anhydrous ethanol were mixed in a mass ratio of 1:3.8:2.2, and wet-milled at a speed of 310 r / min for 1.8 h to obtain CBS precursor wet material; the CBS precursor wet material was dried at 78° C. for 2.2 h to obtain CBS precursor dry material; the CBS precursor dry material was calcined, ground and sieved through a 180-mesh sieve in sequence to obtain CBS powder;
[0201] The calcination process of the CBS precursor dry material includes the following steps:
[0202] First, the CBS precursor dry material was heated to 458°C at a heating rate of 128°C / h and kept at this temperature for 1.9h, then continued to be heated to 968°C at a heating rate of 598°C / h and kept at this temperature for 1.9h, and finally cooled to 628°C at a cooling rate of 88°C / h and kept at this temperature for 0.8h. After the end of the holding period, it was cooled to room temperature in the furnace.
[0203] (6) mixing aluminum oxide, aluminum nitride, the cordierite powder obtained in step (4), the CBS powder obtained in step (5), yttrium oxide, cerium oxide and lanthanum oxide uniformly to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 48wt%, the mass fraction of aluminum nitride is 33wt%, the mass fraction of cordierite powder is 9.5wt%, the mass fraction of CBS powder is 3.9wt%, the mass fraction of yttrium oxide is 2.4wt%, the mass fraction of cerium oxide is 0.6wt%, and the mass fraction of lanthanum oxide is 2.6wt%;
[0204] The precursor mixture, abrasive balls and deionized water prepared above were mixed in a mass ratio of 1:1.95:0.58, and wet ball milled at a speed of 330 r / min for 1.8 h to obtain a precursor wet material; the precursor wet material was dried at 88° C. for 9 h, and then crushed and ground, and after grinding, passed through a 158 mesh sieve to obtain a precursor dry powder;
[0205] (7) mixing the precursor dry powder obtained in step (6) with 42 g / L polyvinyl butyral solution to obtain a precursor solution, wherein the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:0.095;
[0206] The precursor solution prepared above was subjected to spray granulation to obtain precursor powder, wherein the inlet temperature of the spray granulation was 258° C., the outlet temperature was 115° C., and the feed flow rate was 28 mL / min; the precursor powder was placed in a mold, and tabletted at 42 MPa for 8 seconds to obtain a green body;
[0207] (8) calcining the green body obtained in step (7), the specific steps comprising:
[0208] The green body is heated to 658°C at a heating rate of 125°C / h and kept at this temperature for 2.8h, then continued to be heated to 1530°C at a heating rate of 248°C / h and kept at this temperature for 18min, then cooled to 1358°C at a cooling rate of 298°C / h and kept at this temperature for 7.2h. After the insulation is completed, it is cooled to 98°C in the furnace and then taken out, cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material.
[0209] Example 5
[0210] This embodiment provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0211] (1) heating the talc particles to 1200°C and keeping the temperature for 3 hours, cooling them to room temperature in the furnace to complete the calcination, and crushing, grinding and sieving the calcined talc particles to obtain calcined talc with a particle size D90 of 20 μm;
[0212] (2) heating the kaolin particles to 1000°C and keeping the temperature for 1 hour, cooling them to room temperature with the furnace to complete the calcination, and crushing, grinding and sieving the calcined kaolin particles to obtain calcined kaolin with a particle size D90 of 3 μm;
[0213] (3) the calcined talc obtained in step (1), the calcined kaolin obtained in step (2), aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain a cordierite precursor powder, wherein the mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is 38:49:20, the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass ratio of vanadium pentoxide is 1:0.05, and the mass ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to calcium fluoride is 1:0.1;
[0214] (4) The cordierite precursor powder prepared in step (3), abrasive balls and deionized water are mixed in a mass ratio of 1:1.6:0.8, and wet-milled at a speed of 300 r / min for 2 h to obtain a cordierite precursor wet material; the cordierite precursor wet material is dried at 80° C. for 2 h to obtain a cordierite precursor dry material; the cordierite precursor dry material is calcined, ground and sieved through a 200-mesh sieve in sequence to obtain a cordierite powder;
[0215] The calcination process of the cordierite precursor dry material includes the following steps:
[0216] First, the cordierite precursor dry material was heated to 300°C at a heating rate of 250°C / h, then continued to be heated to 900°C at a heating rate of 400°C / h, then continued to be heated to 1360°C at a heating rate of 130°C / h and kept at this temperature for 1.5h, and then cooled to room temperature with the furnace after the end of the heat preservation;
[0217] (5) Calcium carbonate, boric acid and silicon dioxide are mixed uniformly in a mass ratio of 3.2:3:1 to obtain CBS precursor powder; CBS precursor powder, grinding balls and anhydrous ethanol are mixed in a mass ratio of 1:4:2.5, and wet-milled at a speed of 320 r / min for 1.5 h to obtain CBS precursor wet material; the CBS precursor wet material is dried at 80° C. for 2 h to obtain CBS precursor dry material; the CBS precursor dry material is calcined, ground and sieved through a 200-mesh sieve in sequence to obtain CBS powder;
[0218] The calcination process of the CBS precursor dry material includes the following steps:
[0219] First, the CBS precursor dry material was heated to 460°C at a heating rate of 130°C / h and kept at this temperature for 1.8h, then continued to be heated to 970°C at a heating rate of 600°C / h and kept at this temperature for 1.8h, and finally cooled to 630°C at a cooling rate of 90°C / h and kept at this temperature for 0.5h, and then cooled to room temperature with the furnace after the end of the holding period;
[0220] (6) mixing aluminum oxide, aluminum nitride, the cordierite powder obtained in step (4), the CBS powder obtained in step (5), yttrium oxide, cerium oxide and lanthanum oxide uniformly to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 50wt%, the mass fraction of aluminum nitride is 30wt%, the mass fraction of cordierite powder is 10wt%, the mass fraction of CBS powder is 4.2wt%, the mass fraction of yttrium oxide is 2.6wt%, the mass fraction of cerium oxide is 0.6wt%, and the mass fraction of lanthanum oxide is 2.6wt%;
[0221] The precursor mixture, abrasive balls and deionized water prepared above were mixed in a mass ratio of 1:2:0.6, and wet ball milled at a speed of 350 r / min for 1.5 hours to obtain a precursor wet material; the precursor wet material was dried at 90° C. for 8 hours, and then crushed and ground, and after grinding, passed through a 160-mesh sieve to obtain a precursor dry powder;
[0222] (7) mixing the precursor dry powder obtained in step (6) with 45 g / L polyvinyl butyral solution to obtain a precursor solution, wherein the mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:0.1;
[0223] The precursor solution prepared above was subjected to spray granulation to obtain precursor powder, wherein the inlet temperature of the spray granulation was 260° C., the outlet temperature was 120° C., and the feed flow rate was 30 mL / min; the precursor powder was placed in a mold, and tabletted at 45 MPa for 5 seconds to obtain a green body;
[0224] (8) calcining the green body obtained in step (7), the specific steps comprising:
[0225] The green body is heated to 660°C at a heating rate of 130°C / h and kept at this temperature for 2.5h, then continued to be heated to 1550°C at a heating rate of 250°C / h and kept at this temperature for 15min, then cooled to 1360°C at a cooling rate of 300°C / h and kept at this temperature for 7h. After the insulation is completed, the green body is cooled to 100°C in the furnace and then taken out, and cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material.
[0226] Comparative Example 1
[0227] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (3), the ratio of the total mass of calcined talc, calcined kaolin and aluminum hydroxide to the mass of vanadium pentoxide is adjusted to 1:0.02, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0228] Comparative Example 2
[0229] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (3), the ratio of the total mass of calcined talc, calcined kaolin and aluminum hydroxide to the mass of vanadium pentoxide is adjusted to 1:0.06, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0230] Figure 2 The XRD spectra of the cordierite powders prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in FIG. Figure 2 It can be seen that with the increase of the amount of vanadium pentoxide added, the peak value of the intermediate phase magnesia alumina spinel gradually decreases, and the peak value of the cordierite phase gradually increases, which indicates that the addition of vanadium pentoxide to the cordierite powder raw material can promote the synthesis of the cordierite phase. This is because after adding an appropriate amount of vanadium pentoxide to the cordierite powder raw material, it can promote the production of more liquid phase during the sintering process, thereby facilitating ion diffusion, accelerating solid phase reaction, and reducing the generation of the intermediate phase magnesia alumina spinel phase, so that the phase in the cordierite powder after sintering is a relatively pure cordierite phase.
[0231] Figure 3 and Figure 4 The scanning electron microscope images of the cordierite powder prepared in Example 1 and Comparative Example 2 are shown in FIG. Figure 3 In the test, the surface of cordierite powder is a regular block crystal with only a small amount of glass phase. The crystal phase grows well, and the grains grow closely together. There are no obvious holes, cracks, pores and other defects, which is more conducive to obtaining cordierite powder with low dielectric loss. Figure 4 In the embodiment, the grain shape of the cordierite powder is irregular, and a large number of irregular holes, cracks and pores are generated between the grains, resulting in an increase in the dielectric loss of the cordierite powder. This is because the amount of vanadium pentoxide added in Comparative Example 2 is too high. Vanadium pentoxide is volatile and easily soluble in water, and decomposes during high-temperature sintering, resulting in a large number of pores. At the same time, excessive addition of vanadium pentoxide will cause serious deformation of the cordierite powder, thereby generating defects such as cracks, holes, etc. with larger gaps and more numbers inside.
[0232] Comparative Example 3
[0233] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (5), the mass ratio of calcium carbonate, boric acid and silicon dioxide is adjusted to 2.8:2.8:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0234] Comparative Example 4
[0235] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (5), the mass ratio of calcium carbonate, boric acid and silicon dioxide is adjusted to 3.5:2.8:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0236] Comparative Example 5
[0237] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (5), the mass ratio of calcium carbonate, boric acid and silicon dioxide is adjusted to 3:2.5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0238] Comparative Example 6
[0239] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (5), the mass ratio of calcium carbonate, boric acid and silicon dioxide is adjusted to 3:3.2:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0240] Figure 5 , Figure 6 and Figure 7 The scanning electron microscope images of CBS powders prepared in Comparative Example 5, Example 1 and Comparative Example 6 are shown in FIG. Figure 5 In the CBS powder, the crystals are angular and staggered, surrounded by a large amount of glass phase, and have large interconnected pores, a relatively loose structure, and a high dielectric loss. Figure 6 When the amount of boric acid increases, the amount of B2O3 generated increases, which leads to larger grains of CBS powder, more crystal phases, denser structure, and lower dielectric loss. Figure 7 In the experiment, the grains of CBS powder are relatively coarse, and the grains are wrapped with pores and part of the glass phase. There are almost no large holes and gaps, and the structure is more compact. However, due to the excessively high B2O3 content in CBS powder, the content of CaSiO3 crystal phase will decrease, while the content of CaB2O4 crystal phase will increase. Compared with CaB2O4 crystal phase, CaSiO3 crystal phase has higher dielectric properties. Therefore, with the increase of B2O3 content in CBS powder, although the sintering density of CBS powder will be improved, the content of CaSiO3 crystal phase with higher dielectric properties will decrease, which will eventually cause the dielectric properties of CBS powder to decrease.
[0241] Comparative Example 7
[0242] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (6), the mass fraction of cordierite powder in the precursor mixture is adjusted to 8wt%, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0243] Comparative Example 8
[0244] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (6), the mass fraction of cordierite powder in the precursor mixture is adjusted to 12wt%, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0245] Comparative Example 9
[0246] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (6), the mass fraction of CBS powder in the precursor mixture is adjusted to 2 wt %, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0247] Comparative Example 10
[0248] This comparative example provides a method for preparing a low dielectric loss tangent ceramic material for system-level packaging. The difference from Example 1 is that in step (6), the mass fraction of CBS powder in the precursor mixture is adjusted to 5wt%, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0249] Figure 8 , Fig. 9 and Fig.10 The scanning electron microscope images of the ceramic materials prepared in Example 1, Comparative Example 9 and Comparative Example 10 are shown in FIG. Fig. 9 and Fig.10 In the process, a large number of defects such as holes and gaps appeared inside the ceramic material. Figure 8 The internal structure of the ceramic material is dense. This is because when an appropriate amount of CBS powder is added, the liquid phase in the sintering process increases, and the liquid phase infiltrates and fully fills the gaps between the raw material powder particles. Under the action of capillary pressure, the liquid phase tightens the adjacent raw material powder particles, shortening the distance between them, and ultimately resulting in a denser internal structure and lower dielectric loss for the fired ceramic material. However, in Comparative Example 9, due to the small amount of CBS powder added, the amount of liquid phase generated is reduced, so that the surface of the powder particles cannot be fully wetted and wrapped by the liquid phase, and ultimately the structure of the fired ceramic material is loose and the density is poor. Fig. 9In Comparative Example 10, due to the excessive addition of CBS powder, cristobalite precipitates, which weakens the liquid phase sintering effect, and also causes the structure of the ceramic material to become loose and the density to become poor. Fig.10 It can also be seen that a large number of holes and gaps appear inside the ceramic material.
[0250] The flexural strength, thermal expansion coefficient and dielectric loss of the ceramic materials prepared in Examples 1-5 and Comparative Examples 1-10 were tested. The specific test steps are as follows:
[0251] (1) Bending strength
[0252] The present invention uses a three-point bending method and a triaxial shear force instrument to test the flexural strength of the ceramic materials prepared in Examples 1-5 and Comparative Examples 1-10. Before the test, the ceramic material is cut into a strip sample with a length of about 25 mm, and the strip sample is fixed on the triaxial shear force instrument. Then, a concentrated load is applied to the strip sample between two fulcrums. In the absence of impact, the load is gradually increased until the strip sample breaks, and the breaking load is recorded. The flexural strength of the sample is calculated by the following formula:
[0253]
[0254] Where σ is the bending strength of the specimen (MPa), F is the breaking load (N), L is the support distance (cm), b is the cross-sectional width of the specimen (cm), and h is the cross-sectional height of the specimen (cm).
[0255] (2) Thermal expansion coefficient
[0256] The present invention uses a thermal expansion instrument to test the thermal expansion performance of the ceramic materials prepared in Examples 1-5 and Comparative Examples 1-10. Before the test, the ceramic material is cut into a strip sample with a length of about 25 mm, and both ends are polished. The strip sample is fixed on the thermal expansion instrument. In an air atmosphere, the strip sample is heated from ambient temperature to 750°C at a heating rate of 10°C / min, and the elongation of the strip sample caused by heating is recorded to obtain a thermal expansion curve of the elongation of the strip sample and the heating temperature. The thermal expansion coefficient of the sample in the heating range is calculated by the following formula:
[0257]
[0258] Where α is the thermal expansion coefficient of the sample to be tested from T0 to T (K -1 ), T0 is the initial temperature (K), T is the final temperature (K), L0 and L are the lengths of the sample to be tested when the temperatures are T0 and T, respectively (mm).
[0259] (3) Dielectric loss
[0260] Dielectric loss is an indicator that measures the energy loss of a dielectric under the action of an electric field. If the dielectric loss is low, the integrity of the signal transmitted in the packaging material is better; otherwise, the integrity is poor. Therefore, an ideal packaging material should have a lower dielectric loss. The test method for dielectric loss is as follows:
[0261] Silver paste was evenly coated on the surface of the sample, and then placed in an oven for drying. The dried sample was placed on a broadband dielectric impedance meter to measure its dielectric loss. Before the test, the broadband dielectric impedance meter needed to be calibrated to ensure the accuracy of the measurement. The measurement frequency was 10 6 Hz, the dielectric loss value of the sample is directly read from the broadband dielectric impedance meter.
[0262] The test results are shown in Table 1.
[0263] Table 1 Performance test results of ceramic materials prepared in Examples 1-5 and Comparative Examples 1-10
[0264]
[0265] It can be seen from the test data provided in Table 1 that the bending strength of the ceramic materials prepared in Examples 1-5 of the present invention is much higher than that of Comparative Examples 1-10, the thermal expansion coefficient is much lower than that of Comparative Examples 1-10, and the dielectric loss is also much lower than that of Comparative Examples 1-10, which indicates that the ceramic material prepared by the preparation method provided by the present invention has excellent mechanical properties, thermal properties and dielectric properties.
[0266] It can be seen from the test results of Example 1, Comparative Example 1 and Comparative Example 2 that the flexural strength of the ceramic materials prepared in Comparative Example 1 and Comparative Example 2 is much lower than that in Example 1, and the dielectric loss is much higher than that in Example 1. This is because the amount of vanadium pentoxide added in Comparative Example 1 is too little, and the amount of vanadium pentoxide added in Comparative Example 2 is too much, which affects the structural density of the cordierite powder and even causes serious deformation of the cordierite powder, thereby resulting in a significant decrease in the dielectric properties and mechanical properties of the cordierite powder, and ultimately causing a significant decrease in the flexural strength of the ceramic material and a significant increase in the dielectric loss.
[0267] It can be seen from the test results of Example 1, Comparative Example 3 and Comparative Example 4 that the dielectric loss of the ceramic materials prepared in Comparative Example 3 and Comparative Example 4 is much higher than that in Example 1. This is because the amount of calcium carbonate added in Comparative Example 3 is too little, and the amount of calcium carbonate added in Comparative Example 4 is too much, which affects the structural density of the CBS powder, thereby causing the dielectric properties of the CBS powder to decrease significantly, and ultimately causing the dielectric loss of the ceramic material to increase significantly.
[0268] It can be seen from the test results of Example 1, Comparative Example 5 and Comparative Example 6 that the dielectric loss of the ceramic materials prepared by Comparative Example 5 and Comparative Example 6 is much higher than that of Example 1. This is because the amount of boric acid added in Comparative Example 5 is too little, and the amount of boric acid added in Comparative Example 6 is too much, which affects the structural density of the CBS powder, thereby causing the dielectric properties of the CBS powder to decrease significantly, and ultimately causing the dielectric loss of the ceramic material to increase significantly. In addition, the thermal expansion coefficient of the ceramic material prepared by Comparative Example 6 is also much higher than that of Comparative Example 1. This is because the amount of boric acid added in Comparative Example 6 is too much, and accordingly, the amount of silicon dioxide added is too low, resulting in too low content of β-CaSiO3 crystal phase, and β-CaSiO3 crystal phase has a lower thermal expansion coefficient, which results in a decrease in the content of β-CaSiO3 crystal phase in the ceramic material prepared by Comparative Example 6 and a significant increase in the thermal expansion coefficient.
[0269] It can be seen from the test results of Example 1, Comparative Example 7 and Comparative Example 8 that the thermal expansion coefficient and dielectric loss of the ceramic material prepared in Comparative Example 7 are much higher than those in Example 1. This is because the amount of cordierite powder added in Comparative Example 7 is too small, which cannot effectively reduce the sintering temperature of the ceramic powder, which is not conducive to the sintering densification process. Therefore, the structure of the ceramic material finally obtained is relatively loose, which ultimately causes the thermal expansion coefficient and dielectric loss of the ceramic material to increase significantly. The flexural strength of the ceramic material prepared in Comparative Example 8 is much lower than that in Example 1, and the thermal expansion coefficient is much higher than that in Example 1. This is because the amount of cordierite powder added in Comparative Example 8 is too much, which promotes the reaction between Al2O3 and AlN to generate Al5O6N impurity phase, and the Al5O6N phase is dispersed at the grain boundary of the Al2O3+AlN solid solution, which ultimately causes the flexural strength of the ceramic material to decrease significantly and the thermal expansion coefficient to increase significantly.
[0270] It can be seen from the test results of Example 1, Comparative Example 9 and Comparative Example 10 that the thermal expansion coefficient and dielectric loss of the ceramic materials prepared in Comparative Example 9 and Comparative Example 10 are much higher than those in Example 1. This is because the amount of CBS powder added in Comparative Example 9 is too small, and the amount of CBS powder added in Comparative Example 10 is too large, so that the surface of the powder particles cannot be fully wetted and wrapped by the liquid phase, which significantly reduces the structural density of the ceramic material, and ultimately causes the thermal expansion coefficient and dielectric loss of the ceramic material to increase significantly.
[0271] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a low dielectric loss tangent ceramic material for system-level packaging, characterized in that: The preparation method comprises: Aluminum oxide, aluminum nitride, cordierite powder, CBS powder and rare earth oxide are uniformly mixed to obtain a precursor mixture, wherein the mass fraction of aluminum oxide in the precursor mixture is 40-50wt%, and the mass fraction of aluminum nitride in the precursor mixture is 30-40wt%; the mass fraction of cordierite powder in the precursor mixture is 9-10wt%, and the mass fraction of CBS powder in the precursor mixture is 3.8-4.2wt%; the rare earth oxide consists of yttrium oxide, cerium oxide and lanthanum oxide, the mass fraction of yttrium oxide in the precursor mixture is 2.4-2.6wt%, the mass fraction of cerium oxide in the precursor mixture is 0.4-0.6wt%, and the mass fraction of lanthanum oxide in the precursor mixture is 2.4-2.6wt%; The precursor mixture, abrasive balls and deionized water are mixed and wet-milled to obtain a precursor wet material, and the precursor wet material is dried and sieved to obtain a precursor dry powder; the precursor dry powder is mixed with a polyvinyl butyral solution to obtain a precursor solution; the precursor solution is spray-granulated to obtain a precursor powder; the precursor powder is placed in a mold for tableting to obtain a green body; the green body is heated to a binder removal temperature and kept warm, and is continuously heated to a first sintering temperature and kept warm, and then cooled to a second sintering temperature and kept warm, and after the insulation is completed, the green body is cooled to a furnace discharge temperature and taken out, and cooled to room temperature outside the furnace to obtain the low dielectric loss tangent ceramic material; The cordierite powder is prepared by the following method: Calcined talc, calcined kaolin, aluminum hydroxide, vanadium pentoxide and calcium fluoride are uniformly mixed to obtain cordierite precursor powder; the cordierite precursor powder, abrasive balls and deionized water are mixed and wet-milled to obtain cordierite precursor wet material; the cordierite precursor wet material is dried to obtain cordierite precursor dry material; the cordierite precursor dry material is sequentially calcined, ground and sieved to obtain the cordierite powder; The ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass of the vanadium pentoxide is 1:(0.03-0.05); The CBS powder is prepared by the following method: The calcium carbonate, boric acid and silicon dioxide are uniformly mixed to obtain a CBS precursor powder; the CBS precursor powder, grinding balls and anhydrous ethanol are mixed and wet-milled to obtain a CBS precursor wet material; the CBS precursor wet material is dried to obtain a CBS precursor dry material; The CBS precursor dry material is calcined, ground and sieved in sequence to obtain the CBS powder; the mass ratio of the calcium carbonate, boric acid and silicon dioxide is (3-3.2):(2.8-3):
1.
2. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The calcined talc is prepared by the following method: The talc particles are heated to 1000-1200° C. and kept at this temperature for 3-5 hours, and then cooled to room temperature along with the furnace to complete the calcination, and the calcined talc particles are crushed, ground, and sieved to obtain the calcined talc; The calcined kaolin is prepared by the following method: The kaolin particles are heated to 900-1000° C. and kept at this temperature for 1-2 hours, and then cooled to room temperature along with the furnace to complete the calcination, and the calcined kaolin particles are crushed, ground, and sieved to obtain the calcined kaolin; The mass ratio of the calcined talc, calcined kaolin and aluminum hydroxide is (37-38):(48-49):(19-20); The particle size D90 of the calcined talc is 18-20 μm; The particle size D90 of the calcined kaolin is 2-3 μm; The ratio of the total mass of the calcined talc, calcined kaolin and aluminum hydroxide to the mass of the calcium fluoride is 1:(0.08-0.1); The mass ratio of the cordierite precursor powder, abrasive balls and deionized water is 1:(1.3-1.6):(0.6-0.8); The rotation speed of the wet ball milling of the cordierite precursor powder, abrasive balls and deionized water is 250-300 r / min; The cordierite precursor powder, abrasive balls and deionized water are wet-milled for 2 to 3 hours; The drying temperature of the cordierite precursor wet material is 70-80°C; The drying time of the cordierite precursor wet material is 2 to 3 hours.
3. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The calcination process of the cordierite precursor dry material comprises the following steps: First, the cordierite precursor dry material is heated to a first calcination temperature at a first heating rate, then continued to be heated to a second calcination temperature at a second heating rate, then continued to be heated to a third calcination temperature at a third heating rate, and kept warm at the third calcination temperature, and cooled to room temperature with the furnace after the insulation is completed, wherein the third heating rate is less than the first heating rate and less than the second heating rate; The first heating rate is 240-250°C / h; The first calcination temperature is 290-300°C; The second heating rate is 390-400°C / h; The second calcination temperature is 890-900°C; The third heating rate is 120-130°C / h; The third calcination temperature is 1350-1360°C; Keeping the temperature at the third calcination temperature for 1.5 to 2.5 hours; The mesh number of the sieve used for the sieving is 150-200 meshes.
4. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The mass ratio of the CBS precursor powder, the abrasive balls and the anhydrous ethanol is 1:(3-4):(1.5-2.5); The rotation speed of the wet ball milling of the CBS precursor powder, grinding balls and anhydrous ethanol is 280-320 r / min; The wet ball milling time of the CBS precursor powder, grinding balls and anhydrous ethanol is 1.5 to 2.5 hours; The drying temperature of the CBS precursor wet material is 70-80°C; The drying time of the CBS precursor wet material is 2 to 3 hours.
5. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The calcination process of the CBS precursor dry material comprises the following steps: First, the CBS precursor dry material is heated to a fourth calcination temperature at a fourth heating rate and kept at the temperature, then continued to be heated to a fifth calcination temperature at a fifth heating rate and kept at the temperature, and finally cooled to a sixth calcination temperature at a first cooling rate and kept at the temperature, and after the insulation is completed, cooled to room temperature with the furnace, wherein the first cooling rate is less than the fourth heating rate and less than the fifth heating rate; The fourth heating rate is 120-130°C / h; The fourth calcination temperature is 450-460°C; Keeping the temperature at the fourth calcination temperature for 1.8 to 2.2 hours; The fifth heating rate is 590-600°C / h; The fifth calcination temperature is 960-970°C; Keeping the temperature at the fifth calcination temperature for 1.8 to 2.2 hours; The first cooling rate is 80-90°C / h; The sixth calcination temperature is 620-630°C; Keeping the temperature at the sixth calcination temperature for 0.5 to 1.5 hours; The mesh number of the sieve used for the sieving is 150-200 meshes.
6. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The mass ratio of the precursor mixture, the abrasive balls and the deionized water is 1:(1.8-2):(0.5-0.6); The rotation speed of wet ball milling of the precursor mixture, abrasive balls and deionized water is 300-350 r / min; The time of wet ball milling of the precursor mixture, abrasive balls and deionized water is 1.5 to 2.5 hours; The drying temperature of the precursor wet material is 80-90°C; The drying time of the precursor wet material is 8 to 12 hours; The mesh number of the sieve through which the precursor wet material is sieved after drying is 150-160 mesh; The polyvinyl butyral solution consists of polyvinyl butyral and anhydrous ethanol; The concentration of polyvinyl butyral in the polyvinyl butyral solution is 35-45 g / L; The mass ratio of the precursor dry powder to the polyvinyl butyral in the polyvinyl butyral solution is 1:(0.08-0.1); The inlet temperature of the precursor solution for spray granulation is 250-260°C; The outlet temperature of the spray granulation of the precursor solution is 100-120°C; The feed flow rate of the spray granulation of the precursor solution is 25-30 mL / min; The tableting pressure of the precursor powder is 35-45 MPa; The tableting time of the precursor powder is 5 to 15 seconds.
7. The method for preparing a low dielectric loss tangent ceramic material for system-level packaging according to claim 1, characterized in that: The heating rate of the green body to the debinding temperature is 110-130°C / h; The debinding temperature is 650-660°C; The holding time at the debinding temperature is 2.5 to 3.5 hours; The heating rate from the debinding temperature to the first sintering temperature is 240-250° C. / h; The first sintering temperature is 1500-1550°C; The holding time at the first sintering temperature is 15 to 25 minutes; The cooling rate from the first sintering temperature to the second sintering temperature is 290-300° C. / h; The second sintering temperature is 1350-1360°C; The holding time at the second sintering temperature is 7 to 8 hours; The furnace temperature is 90-100°C.
8. A low dielectric loss tangent ceramic material for system-level packaging prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-purity alumina ceramic materials and their preparation methods
CN110128117B
Ceramic packaging housing material for low resistance leads
CN110423102A
An alumina ceramic, its preparation method and application
CN115321960B
Cited By
Preparation method of high-thermal-conductivity aluminum nitride ceramic substrate
CN119930300A